2007
DOI: 10.1161/01.hyp.0000255983.32896.b9
|View full text |Cite
|
Sign up to set email alerts
|

Excessive Sympathetic Activation in Heart Failure With Obesity and Metabolic Syndrome

Abstract: Abstract-Congestive heart failure is characterized by sympathetic activation, which has also been described in the metabolic syndrome. No information exists, however, as to whether the sympathostimulating effects of these 2 conditions summate when heart failure is complicated by the metabolic syndrome, leading to an exceedingly high adrenergic drive. This is clinically relevant, because in heart failure sympathetic activation is closely related to mortality. We studied 48 control subjects (age: 58.4Ϯ1.6 years,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
89
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 115 publications
(97 citation statements)
references
References 44 publications
5
89
1
1
Order By: Relevance
“…This theory is supported by the recent publication by Grassi et al that showed MetS potentiates the sympathetic activation in HF. 28 In some studies, which included patients after a MI delayed onset of the mortality effects (after 2 years), it has been observed, 13,21,22 while other studies report mortality effects before 2 years. 12,16 Similar to our results, de Simone et al found a higher risk of death according to diabetic status.…”
Section: Discussionmentioning
confidence: 99%
“…This theory is supported by the recent publication by Grassi et al that showed MetS potentiates the sympathetic activation in HF. 28 In some studies, which included patients after a MI delayed onset of the mortality effects (after 2 years), it has been observed, 13,21,22 while other studies report mortality effects before 2 years. 12,16 Similar to our results, de Simone et al found a higher risk of death according to diabetic status.…”
Section: Discussionmentioning
confidence: 99%
“…Multiunit recording of MSNA was obtained from a microelectrode inserted in a peroneal nerve posterior to the fibular head, as reported previously [6][7][8]12,13,17,18]. Integrated nerve activity was monitored by a loud-speaker, displayed on a storage oscilloscope (model 511A, Tektronix), and continuously recorded with BP and heart rate on an ink polygraph.…”
Section: Measurementsmentioning
confidence: 99%
“…© 2008 European Society of Cardiology. Published by Elsevier B.V. All rights reserved.Keywords: Heart failure; Sympathetic activity; Plasma norepinephrine; Muscle sympathetic nerve traffic; Muscle sympathetic nerve activity Congestive heart failure (CHF) is characterized by a marked sympathetic activation which is 1) directly proportional to the severity of the CHF state [1][2][3][4][5][6], 2) of similar magnitude in CHF of ischaemic and idiopathic dilated aetiology [7], 3) affects several vascular circulations such as the cerebral, the coronary, the muscle and the renal ones [6,7-11], 4) potentiated when other clinical conditions also characterized by adrenergic overdrive, such as hypertension, obesity and metabolic syndrome, are concomitantly present [12,13], and 5) relevant for patient's prognosis because it is inversely related to survival rate [2,[14][15][16]. The adrenergic overdrive characterizing the CHF syndrome is detectable by both indirect and direct approaches to assess sympathetic tone, such as plasma norepinephrine (NE) assay, NE spillover technique as well as microneurographic recording of efferent postganglionic muscle sympathetic nerve activity (MSNA) [1][2][3][4][5][6][7][8][9][10][11].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, more researchers are paying attention to MetS, and more studies on its mechanism are being carried out. MetS is associated with sympathetic activation4, 5, 6. A previous study found that MetS is a state of peripheral sympathetic nerve hyperactivity7.…”
Section: Introductionmentioning
confidence: 99%